Validity and Reliability Evidence for Assessments Based in Applied Behavior Analysis: A Systematic Review. Issue 1 (January 2023) - Padilla, Kristen L.; Weston, Regan; Morgan, Grant B.; Lively, Providence; O'Guinn, Nicole
The current article presents the findings from a systematic review of the available reliability and validity evidence supporting the use of criterion-referenced assessments based on the applied behavior analysis framework. We identified 46 studies that reported reliability and/or validity evidence for six assessments, 37 of which presented reliability evidence and 43 presented validity evidence. Additionally, we extracted and summarized information related to participant characteristics (e.g., age, sex, diagnosis), geographic location, and research setting (e.g., residential facility, home). Overall, we found conflicting support for the use of the assessments. When coupled with the reported usage by behavior analysis professionals, our findings suggest a misalignment between the reportedly used assessments and the number of published studies providing validity and/or reliability evidence. We found inconsistent use of measurement-related vocabulary and that many studies could have been strengthened by conducting different statistical analyses. We provide a summary of studies, findings, and offer recommendations for clinical practice and future measurement research.